Por uma civilização cristã : a coleção monsenhor Álvaro Negromonte e a pedagogia do catecismo (1937 - 1965) - Orlando, Evelyn de Almeida (2008)
This work investigates the collection of the catechisms of Monsignor Álvaro Negromonte published between 1937 and 1965, under two perspectives of analysis: in his material support in the context of the editorial market to the season and in his content through the approximations with the presupposed of the New School. Starting from these two points of analysis the research tries to help with a shading scenery in the area of the History of Brazilian Education that don t comes looking to the catechism as a class of printed that determined much times the Brazilians school practices. Inserted in the area of the History of Education, the investigation begins from the proposal of the Cultural History and from the History of the Book, even looking to the history of the collections, that consider the book of catechism as any book, a cultural object, that wants to promote the civilization process by the education. The Collection Monsignor Álvaro Negromonte is composed of 14 volumes: 12 titles destined to the teaches of schools since the 1st grade of elementary school until the regular course and 3 Guides of the Catechist: the 1st referring to the orientation of catechism teaching for the 1st and 2nd grades of elementary school; the 2nd guide referring to the 3rd grade of elementary school; and the 3rd guide orientated the 4th grade of elementary school. The general purpose of this investigation is based on analyzing this collection as a didactic tool used by the Catholic Church to the formation of the individuals. The materiality, the production, the circulation and the appropriation guided the way that composed scenery that the religious area acted trying to create a Christian civilization. Through the modern practices that the Church developed as the using of printed, in this case, the catechism, a specific object of transmission of the Catholic culture, little explored in the researches in History of Education yet, as in its materiality as in the representations that acquired in the Brazilian society, this research has yet the presence and the place of the Catholic Church in the educational discussions that happened in the country between the decades of 30 and 60 of the 20th century and the appropriation of the discussion about the Actives Pedagogies for this group defended by the author of the collection.